A SYSTEMATIC LITERATURE REVIEW ON THE CYBERSECURITY GAPS IN SAUDI CURRICULUM THAT AFFECT THE BANKING SECTOR. - Mishra, Dr Renu; Hanna, Antoine H. (The journal of contemporary issues in business and government, 2023)
The accessibility of top-notch cybersecurity education directly impacts knowledge of potential hazards from cyberattacks, which could raise awareness among bank employees and account holders when utilising bank applications and portals. This paper outlines a systematic literature review (SLR) of peer-reviewed conference and journal articles published from 2005 to 2022. It focuses on the role of Saudi Arabia's Vision 2030 in enhancing the educational system, the high demand for cybersecurity experts due to the country's economic transformation, and the role of universities in raising cybersecurity awareness before identifying gaps in existing research. Eighty- seven documents discussing cybersecurity in the Kingdom were found after four digital libraries were checked. The findings show that additional survey research is required to establish a theoretical knowledge of higher education's contribution to addressing cybersecurity issues in the banking industry. The three primary variables of this research (cybersecurity, education, banks) developed in this paper can serve as a guide for researchers and bank managers.